Cold mix asphalt design with ternary cementitious fillers to reduce loss of stability due to moisture - Hernández Moreno, Julio César (2023)
The use of cold asphalt mixtures has aroused interest in recent years because it is a technique that reduces the use of fuels and thus the carbon footprint in the construction and maintenance of pavements, however its use has been limited in patching applications and low-traffic pavements, however, these mixtures have low resistance at an early age and high amounts of voids. The objective of this research was the development of a cold mixture with replacement of the mineral filler with ternary cementitious fillers that together form hydration products and provide greater resistance in the presence of water. The ternary cementitious fillers are composed of granulated blast furnace slag (EGAH), fly ash (CV) and an alkaline activator, Portland cement (CP) or calcium hydroxide (lime), in order to compare which of these activators provides greater performance different mixtures were prepared with partial and total substitution, to evaluate in three curing conditions and observe the behavior of the mixtures in the presence of water. It was proven that replacement with both types of cementitious fillers significantly reduces the effects of moisture at an early age. For the curing condition of 3 days at 25 °C, the reference sample obtained a loss of stability of 30,78 %, the samples with CP of 7,61 and 7,56 %, and those of lime with 13,83 and 16,39 %, have a lower loss of stability in all cases, this same pattern is maintained over time.